Impact of assessment of fractional flow reserve and instantaneous wave-free ratio on clinical outcomes of percutaneous coronary intervention: a systematic review, meta-analysis and meta-regression analysis - E. Z. Golukhova; K. V. Petrosian; A. V. Abrosimov; N. I. Bulaeva; E. S. Goncharova; B. Sh. Berdibekov (Российский кардиологический журнал)
Aim. To conduct a systematic review and meta-analysis to compare clinical outcomes in patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI) using conventional coronary angiography (CAG) or fractional flow reserve (FFR)-guided PCI. In addition, FFR-guided PCI and PCI guided with instantaneous wave-free ratio (iFR) were compared.Material and methods. PubMed, Google Scholar databases were searched for studies comparing clinical outcomes in patients with CAD undergoing CAG-guided or FFR/iFR-guided PCI. Dichotomous data analysis was presented as odds ratio (OR) with 95% confidence interval (CI). Adjusted hazard ratio (HR) values from studies with similar evaluation criteria were pooled for meta-analysis.Results. Six randomized controlled trials (RCTs) from 184 publications were selected for this systematic review and meta-analysis. A total of 2193 patients (mean age, 64,2 years, mean follow-up, 28,0 months) were included. Analysis of RCTs showed that CAG-guided and FFR-guided PCI did not have a significant difference in the incidence of major adverse cardiovascular events (MACE) (OR: 0,78; 95% CI: 0,61-1,00; p=0,05; I2=0%), all-cause death (OR: 0,86; 95% CI: 0,51-1,44; p=0,57; I2=0%) or emergency revascularization (OR: 0,69, 95% CI: 0,46-1,04, p=0,08, I2=0%). However, FFR-guided PCI was associated with a reduced risk of subsequent MI compared with CAG-guided PCI (OR: 0,70; 95% CI: 0,50-0,99; p=0,04; I2=0%). In addition to the results of previous RCTs, we conducted a metaanalysis of 3 observational studies. In total, the CAG-guided and FFR-guided PCI groups included 165012 and 11450 patients, respectively. A meta-analysis showed that FFR-guided PCI was associated with a reduced risk of all-cause mortality (HR: 0,74; 95% CI: 0,63-0,87; P=0,0003) and MI (HR: 0,75; 95% CI: 0,61-0,94; p=0,01). In addition, there was no significant difference between iFRand FFR-guided PCI in terms of MACE (OR: 0,97; 95% CI: 0,76-1,23; p=0,81), all-cause mortality (OR: 0,66; 95% CI: 0,40-1,10; p=0,11), MI (OR: 0,83; 95% CI: 0,56-1,24; p=0,37) or emergency repeated revascularization (OR: 1,16; 95% CI: 0,85-1,58; p=0,34).Conclusion. FFR-guided PCI is associated with a reduced risk of all-cause mortality and subsequent MI compared with CAG-guided PCI. At the same time, the iFR-guided PCI is not inferior to the FFR-guided method in terms of MACE rate.